The Influence of Marketing Mixture on Purchase Us Decision of Used Clothing (Study at Online Shop @mejasoklat) - Erfan, Mochamad (Eco-Entrepreneur, 2023)
In today's increasingly fierce business competition, every company is required to be able to compete and set the right marketing strategy. Marketing is one of the most important factors for companies, especially those engaged in goods and services. This study aims to determine the effect of the marketing mix consisting of product, price, place, and promotion on the decision to purchase used clothing at the online thrift shop @mejasoklat. The method used is associative. The research population used was all used clothing buyers at the online thrift shop @mejasoklat, a total of 610 people The sample size is 86 people, and the sampling technique used is simple random sampling. The analysis technique used is multiple regression analysis. The results of the simultaneous analysis of the marketing mix consisting of product, price, promotion, and place have a significant effect on purchasing decisions. While partially, only the marketing promotion mix has a significant effect on purchasing decisions, while product, price, and place have no significant effect on purchasing decisions for used clothes at the online thrift shop @mejasoklat